How do psychologically based interventions for chronic musculoskeletal pain work? A systematic review and meta-analysis of specific moderators and mediators of treatment. (June 2022) - Murillo, Carlos; Vo, Tat-Thang; Vansteelandt, Stijn; Harrison, Lauren E.; Cagnie, Barbara; Coppieters, Iris; Chys, Marjolein; Timmers, Inge; Meeus, Mira
Abstract: Psychologically based interventions aim to improve pain-related functioning by targeting pain-related fears, cognitions and behaviors. Mediation and moderation analyses permit further examination of the effect of treatment on an outcome. This systematic review and meta-analysis aims to synthetize the evidence of specific mediators and moderators (i.e., treatment targets) of psychologically based treatment effects on pain and disability. A total of 28 mediation and 11 moderation analyses were included. Thirteen mediation studies were included in a meta-analysis, and the rest was narratively synthetized. Reductions in pain-related fear (indirect effect [IE]: −0.07; 95% confidence interval [CI]: −0.11, −0.04) and catastrophizing (IE: -0.07; 95%CI: −0.14, −0.00), as well as increases in self-efficacy (IE: -0.07; 95%CI: −0.11, −0.04), mediated effects of cognitive behavioral therapy on disability but not on pain intensity, when compared to control treatments. Enhancing pain acceptance (IE: -0.17; 95%CI: −0.31, −0.03) and psychological flexibility (IE: -0.30; 95%CI: −0.41, −0.18) mediated acceptance and commitment therapy effects on disability. The narrative synthesis showed conflicting evidence, which did not support a robust moderated effect for any of the examined constructs. Overall, the methodological quality regarding mediation was low, and some key pitfalls are highlighted alongside recommendations to provide a platform for future research. Highlights: Reductions in pain-related fear and catastrophizing and increases in self-efficacy mediate effects of CBT on disability but not on pain intensity. Increases of pain acceptance and psychological flexibility mediate ACT effects on disability. Still, there is limited evidence on the shared and separate mechanisms across the psychologically based interventions for pain. Overall, the methodological quality of the available mediation literature is low. Conflicting evidence does not support a robust moderated effect for any of the examined constructs.